Stuttering related and psychosocial predictors of impact of stuttering - Humaira Naz; Rukhsana Kausar (Journal of the Pakistan Medical Association, 2022)
Objective: To investigate the psychosocial factors having an impact on persons with a stuttering problem. Methods: The correlation study was conducted from October 2016 to February 2018 at hospitals, speech clinics and educational institutes of Lahore. The sample was comprised of young adults aged 16-30 years of either gender with development stuttering problem. Data was collected using Stuttering Severity Instrument-4, Social Interaction Anxiety Scale-Urdu, Big Five Measure-20, Overall Assessment of the Speaker’s Experience of Stuttering and the Urdu version of the shortened form of the Coping Orientation to Problems Experienced inventory. Data was analysed using SPSS 23. Results: Of the 78 subjects, 66(84.6 %) were males and 12 (15.4 %) were females. There were 21(27%) subjects aged 16-19 years and 57(73%) with age range of 20 - 30 years. The overall mean age was 21.96 ± 3.89 years. Mean age of onset was 4.59 ± 1.29 years, while gradual onset and progressive stuttering was reported by 74(94.9 %). The Bilingual users 49(63%) reported to have frequent stuttering. Among the 43(55.1%) who had received treatment, 30 (38%) received speech therapy and 26 (33.3%) reported dissatisfaction. Stuttering severity and social anxiety were significantly positively correlated with all domains of impact of stuttering (p<0.05). Age, and duration were negatively correlated with day-to-day communication (p<0.05) and previous speech treatment showed negative association with impact on general knowledge about stuttering (p<0.05). Avoidance coping strategy had a significant relationship with all domains of impact (p<0.05). —Continue